Location, market orientation, and firm performance: An analysis of the Colombian healthcare industry - Amézquita, Juan C (2022)
In the Latin American healthcare industry, there seems to be an association between the implementation of the marketing strategies and the firms' location that suggests the need to study the organizational performance under these aspects. To this end, this paper contrasts the relationships between an organization's market orientation (MO), its location (for example, within a service cluster), and performance. The quantitative analysis was carried out among managers' perceptions from 134 service companies belonging to the healthcare service companies operating in the city of Cali, Colombia. The results showed a positive association between being located in a service cluster and business performance. It was also shown that the strategic approach based on OM positively affects performance. Moreover, we noted that competitors' orientation is the only component of the OM construct that significantly influences performance. The conclusions of our study allow for guiding the strategic decision-making of the managers of these companies regarding the decisions of location and content of marketing strategies.